Do running kinematic characteristics change over a typical HIIT for endurance runners? - Garcia-Pinillos, F.; Soto-Hermoso, V. M.; Latorre-Román, P. Á. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to describe kinematic changes that occur during a common high-intensity intermittent training (HIIT) session for endurance runners. Twenty-eight male endurance runners participated in this study. A high-speed camera was used to measure sagittal-plane kinematics at the first and the last run during a HIIT (4 × 3 × 400 m). The dependent variables were spatial-temporal variables, joint angles during support and swing, and foot strike pattern. Physiological variables, rate of perceived exertion, and athletic performance were also recorded. No significant changes (p = 0.05) in kinematic variables were found during the HIIT session. Two cluster analyses were performed, according to the average running pace—faster vs. slower, and according to exhaustion level reached—exhausted group vs. nonexhausted group (NEG). At first run, no significant differences were found between groups. As for the changes induced by the running protocol, significant differences (p = 0.05) were found between faster and slower athletes at toe-off in ohip and oknee, whereas some changes were found in NEG in ohip during toe-off (+4.3°) and oknee at toe-off (-5.2°) during swing. The results show that a common HIIT session for endurance runners did not consistently or substantially perturb the running kinematics of trained male runners. Additionally, although some differences between groups have been found, neither athletic performance nor exhaustion level reached seems to be determinant in the kinematic response during a HIIT, at least for this group of moderately trained endurance runners.